2018
DOI: 10.14715/cmb/2018.64.14.18
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of date extract on rat nephrotoxicity induced by gentamicin, clinical, histological and antioxidant evidences

Abstract: In this study, it was aimed to investigate the effect of the date extract (Phoenix dactylifera) on certain biochemical parameters and total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index in nephrotoxicity induced by gentamicin. The rats used in the study were randomly selected and divided into 4 groups, each consisting of 8 rats: control group, date extract (DE) group, gentamicin (GEN) group, gentamicin+date extract (GEN+DE) group.Blood samples and kidney tissues were taken 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In addition, myristic acid has revealed a nephroprotective effect by reducing tubular necrosis in an experimental model of AKI 43 . Finally, the fact that extracts obtained from Cocos nucifera and Phoenix dactylifera, palms with fatty acid compositions similar to D-005, have demonstrated protection against gentamicin-induced nephrotoxicity supports our hypothesis 11 , 12 .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, myristic acid has revealed a nephroprotective effect by reducing tubular necrosis in an experimental model of AKI 43 . Finally, the fact that extracts obtained from Cocos nucifera and Phoenix dactylifera, palms with fatty acid compositions similar to D-005, have demonstrated protection against gentamicin-induced nephrotoxicity supports our hypothesis 11 , 12 .…”
Section: Discussionsupporting
confidence: 75%
“…In this sense, the best protection results have been obtained with antioxidant extracts from plants, being administered concomitantly with the AMG, either simultaneously or as a pre-treatment on the same day 10 . Examples of this are the antioxidant extracts from two species of Arecaceae (Cocos nucifera and Phoenix dactylifera) exhibiting protective effects against AKI, which were administered concomitantly with gentamicin 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on rats investigated the antioxidant effect of date fruit extract against gentamicin-induced nephrotoxicity. In this study, they reported that the TAS level that gentamicin decreased in the kidney tissue, increased the date extract (Celik and Irak 2018).…”
Section: Discussionmentioning
confidence: 67%
“…These 2 different ways of reporting urea results had the same significantly changes when we compared Gentamicin treated group with the control group and when Curcumin (CC and LCC) groups were compared with Gentamicin treated group) ( Table 4 , Figure 5 ). Celik et al also found significantly increased biomarkers for renal function after Gentamicin administration [ 70 ]. Whereas the new nanoformulation of curcumin therapy (liposomal Curcumin) had a better efficiency on renal function biomarkers, we consider that liposomal curcumin pretreatment could significantly contribute to the preservation of renal function in Gentamicin induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%